The Role of Teacher Commitment in Mediating the Influence of Organizational Culture and the Principal’s Transformational Leadership on Teacher Performance - Aprilia Susanti; Suwito Eko Parmono; Arief Yulianto; Noor Hudallah; Agus Wahyudin; Wasino (Universitas Negeri Semarang, 2026)
Teacher performance is crucial for schools. The purpose of this study is to analyze the influence of organizational culture and the principal’s transformational leadership on teacher performance, as reinforced by teacher commitment. This is a quantitative study with a population consisting of elementary school teachers throughout Sukorejo Subdistrict. The sampling technique used was proportional cluster sampling. The sample size was calculated using the Slovin formula, resulting in 207 elementary school teachers in the Sukorejo subdistrict. Data collection employed a previously pilot-tested questionnaire consisting of 63 items. The data analysis methods used were descriptive analysis and Structural Equation Modeling (SEM) with the assistance of the AMOS 23 analysis tool. The results of this study indicate that organizational culture, the principal’s transformational leadership, and teacher commitment have a positive and significant effect on teacher performance. Organizational culture and the principal’s transformational leadership have a positive and significant effect on teacher commitment. Teacher commitment mediates the influence of organizational culture and the principal’s transformational leadership on teacher performance. A suggestion for future research is to include mediating variables that have not yet been studied, such as thriving at work and work meaningfulness.